Fostering Scientific Literacy through Integrated STEM Teaching Materials on Basic Laws of Chemistry - Ani Sutiani; Cinta Johanna Tessalonika Pasaribu (Jurnal Tadris Kimiya, 2023)
The research aims to develop integrated teaching materials with a STEM approach to enhance students' scientific literacy, explicitly focusing on Basic Chemical Law Materials. The study utilized a Research and Development (R&D) approach employing the 4D (define-design-development-disseminate) research model. The research instruments included a test to measure students' scientific literacy and a non-test instrument to gather validation data from experts and assess student responses. The findings demonstrated high feasibility percentages, with 91.4% for content, 89% for presentation, 93.2% for language, 86.6% for scientific literacy, 93.2% for STEM, and 90% for media. Moreover, based on the scientific literacy test results, the N-gain pre-test and post-test indicated a substantial increase with a score of 0.74, classifying it as a high increase. Consequently, it can be concluded that developing integrated teaching materials with a STEM approach effectively enhances students' scientific literacy in basic laws of chemistry.